Out of this Struggle The Filipinos in Hawaii - Teodoro, Luis V. (University of Hawai'i Press, 1981)
In his preface, Danilo E. Ponce describes this book as an "unblinking look at Filipino history in Hawaii." Written from a Filipino viewpoint, the book commemorates seventy five years of collective existence of this ethnic group in the Aloha State. It examines Filipino experience in Hawaii in the context of Philippine history and culture. This is not a simple book, for its subject is complex. For example, there were three waves of Filipino immigration to Hawaii - each wave bringing people of differing socio-economic, educational, and geopolitical backgrounds. It would be misleading to speak of one homogeneous group called "Filipinos" being affected at any given time. Implicit in Out of This Struggle is the human drama that underlies events. Hawaii's need for labor promised the Filipinos the possibility of bettering their economic status, but plantation wages proved so low that entire families needed to work to live, limiting their access to education. Out of this frustration came their active and telling role in the organization of the IL WU and the labor strife of the 1920s. As Hawaii's Filipinos look to the future beyond 1981, they find in their community many and varied elements-proof of vitality, of a community trying to identify issues, examine events, and understand itself. Out of This Struggle will contribute to that understanding. This book is one of the projects of the Filipino 75th Anniversary Commemoration Commission, which was created by the 1977 Hawaii State Legislature, through Enabling Act 181, to oversee the year-long celebration of the arrival of the first Filipinos in Hawaii in 1906. The idea of the Commission itself came from a group called the Hawaii Filipino-American Community Foundation, which, as early as 1976, had thought of the need to celebrate the 75th anniversary of Filipino immigration to Hawaii not only through ceremony, but more appropriately, through more permanent means. One of these means was to be a book which would give its readers some understanding of what the past 75 years have meant for the Filipinos in Hawaii. At the same time, 'the members of the Foundation felt that such a book would adequately mirror the changes that have taken place in the Filipino community, as well as lay to rest the prevalent view that the old stereotypes still apply. The members of the Education (Printed) Committee of the Commission, whose task was to oversee the production of this book, are, fittingly, also members of the Foundation.